Borehole Ground Heat Exchangers and The Flow of Underground Water - Iosif-Stylianou, Iosifina; Christodoulides, Paul; Aresti, Lazaros; Tassou, Savvas A.; Florides, Georgios A. (My University, 2018)
Vertical Ground Heat Exchangers (GHEs) in boreholes are a major form of Geothermal Energy applications. When water flowing underground past the borehole the heat injection rates of the GHE are subject to change. Here, we construct a mathematical model for such regimes. Then, based on the Finite Element Method we construct a corresponding computational model, which is validated with experimental data of a Thermal Response Test carried out in Lakatameia, Cyprus. Finally, using the validated model, the thermal behavior of borehole GHEs is investigated by studying the effect of the (a) BH radius, (b) U-tube diameter, (c) U-tube leg and BH centers distance, (d) grout thermal conductivity and (e) underground water velocity.
Keywords: Ground Heat Exchangers; Borehole; Undergroundwater flow; Geothermal energy; Computational modeling